ChemInform Abstract: RNi8Si3 (R: Gd, Tb): Novel Ternary Ordered Derivatives of the BaCd11 Type. Issue 12 (March 2016) - Pani, M.; Morozkin, A. V.; Yapaskurt, V. O.; Provino, A.; Manfrinetti, P.; Nirmala, R.; Malik, S. K.
Abstract: The title compounds are prepared by arc melting of stoichiometric amounts of the elements under Ar followed by annealing (Ta foil in evacuated silica tubes, 1273 K, 5—7 d).